CHARACTER AND THE STRUGGLE FOR IVILIZATION IN WILLIAM GOLDING'S LORD OF THE FLIES - Miranda, Mai; Wulan, Sri (JOURNAL OF LANGUAGE, 2025)
William Golding's Lord of the Flies (1954) presents a profound exploration of human nature under duress, centering on the collapse of social order and the descent into primal savagery. This study employs a descriptive qualitative method to conduct a character analysis of the novel's protagonist, Ralph, focusing on the intrinsic qualities that define his struggle for survival and the preservation of civilization. Through a close reading of the text, this paper identifies and examines four cardinal traits—leadership, charisma, organizational prowess, and civility—that constitute Ralph's character. The analysis demonstrates that these traits are not merely descriptive but are the fundamental engines of his resistance against the antagonistic force, represented by Jack, which embodies chaos and violence. The findings reveal that Ralph's struggle is multifaceted: it is a physical battle for survival, a psychological fight against despair, and an ideological conflict for the soul of the community. Ultimately, this paper argues that Ralph's characterization serves as Golding's central argument for the fragility of civilization, which must be consciously and courageously upheld through rational principles, democratic leadership, and moral fortitude, even in the face of overwhelming barbarism. His survival is a testament to the resilience of these values.